Application of the TPR (TOTAL PHYSICAL RESPONSE) Method to Increase Maharoh Al Kalam of Grade 10 Students at Madrasah Aliyah: Penerapan Metode TPR (TOTAL PHYSICAL RESPONSE) untuk Meningkatkan Maharoh Al Kalam Siswa Kelas 10 di Madrasah Aliyah - Dewi, Siti Ana; Anwar, Najih (Indonesian Journal of Education Methods Development, 2022)
This article discusses the application of the TPR (Total Physical Response) method to increase the maharoh al kalam of class X students at MA Al Karimi Gresik. The background of this research is that the learning of maharoh kalam in class 10 of MA Al Krimi Gresik is still far from ideal. Understanding of maharoh kalam in Arabic subjects is still low (grade average 49.61). In addition, the number of students who managed to reach and exceed the KKM was less than 75%. The KKM for Arabic subjects at MA Al Karimi is 74. So in this study the researcher offers the TPR (Total Physical Response) method as an alternative that can be used to increase maharoh al Kalam. The purpose of this study was to determine the application of the TPR method in increasing maharoh al-Kalam students of class X MA al-Karimi. The research method used is collaborative experimental classroom action research. The research approach in this study uses a qualitative and quantitative approach. Data collection techniques used are test techniques, observation techniques, and documentation techniques. The data analysis technique used is drawing conclusions and analysis in the form of numbers. And based on the results obtained by the researchers as follows: 1) the application of the TPR method in learning speaking skills in grade 10 was successful. This can be seen from the results of the application of the method in the second cycle, namely with an average class value of 80.26 and a learning percentage of 79%, which is more than 75% of students who are able to achieve the KKM. 2) the application of the TPR method can be done to increase maharoh al kalam in grade 10 at MA Al Karimi.